Avaliação da resposta ao bacilo de Calmette-Guérin no câncer de bexiga utilizando a hibridização in situ com fluorescência (FISH) - Messetti, Fabrizio Magaldi [UNIFESP] (2016)
Objective: To verify, in patients after transurethral resection for high-risk nonmuscle invasive bladder cancer the power of fluorescence in situ hybridization test on predicting bacillus Calmette-guérin immmunotherapy failure. Methods: This was a prospective clinical trial where 100 patients with indication of adjuvant therapy with BCG after TURB for bladder cancer. Four Fluorescence in situ hybridization tests were performed. FISH tests were performed before bacillus Calmette-Guérin, and at 6 weeks, 3 months and 6 months during bacillus Calmette-Guérin therapy with maintenance. Results A total of 100 patients participated in the study. At a median follow-up of 19 months 39% of patients had recurrent tumors and 18% experienced disease progression. Patients who had positive fluorescence in situ hybridization results during bacillus Calmette-Guérin therapy were 3 to 5 times more likely than those who had negative fluorescence in situ hybridization results to experience recurrent tumors (p <0.01). The timing of positive fluorescence in situ hybridization results also affected outcomes. Conclusions: Fluorescence in situ hybridization results can identify patients at risk for tumor recurrence and progression during bacillus Calmette-Guérin immunotherapy. This information may be used to counsel patients about alternative treatment strategies.